A study of the leaves of Manihot esculenta Crantz (Family Euphorbiaceae) - Loyola, Ruth
The leaves of the Manihot esculenta Crantz was finely crushed and powdered. The material was added with 95% ethyl alcohol and a simple extraction procedure was done on it. The alcoholic extract was then analyzed by thin layer and column chromatography.